LITERATURE REVIEW: THE IMPLEMENTATION OF E-HEALTH AT PRIMARY HEALTHCARE CENTERS IN SURABAYA CITY - Yesica Aprillia Putri; Wasis Budiarto (Universitas Airlangga, 2020)
Background: The increasing number of patient visits in primary healthcare centers in Surabaya causes long duration of queue in a registration counter. To solve this problem, Surabaya Government has created an online registration system in each health service provider. The e-health is expected to give a positive impact on reducing the queue traffic at the registration counter.Aim: This study identified whether the online registration system or e-health which has been implemented by primary healthcare centers in Surabaya City is successful or not.Method: This study was a literature review which collected articles from Google Scholar databases published from 2015 until 2019. Fourteen articles were collected, but only 6 articles were discussed because of their relevant topics.Results: The review shows that e-health can simplify the process of patient registration and reduce patients’ waiting time for health service delivery. The success indicators of e-health program include its well-established system, effective information system, and excellent service for community. Obstacles found in the e-health implementation involve lack of thorough socialization of e-health. In turn, the community prefers a manual registration to e-health.Conclusion: The e-health service in primary healthcare centers in Surabaya City gives a positive effect on giving a fast and easy process in the registration procedure. However, there are still obstacles in implementing e-health due to lack of socialization. Keywords : queue, e-health, queuing time, primary healthcare centers.